Study of depression risk in geriatric population of urban area of Pune, India - Ritesh P. Kundap; Samir Singru; Kevin Fernandez (Al Ameen Medical College, 2016)
Introduction: As age advances there is increased morbidity and functional loss. A variety of depressive factors and occurrence of varying life events, greatly impact on one's psychological status, making the elderly more prone to depression. Decreased care & attention, economic dependence and unorganised geriatric health services are adding to the morbidity. Objective: To study the prevalence of depression risk in the elderly population aged 65 yrs and above and identify various risk factors. Material & Methods: Study design: Cross sectional study. Study area: Urban field practice area of SKNMC & GH. Sample size and sampling technique: with 95 % confidence interval & 5 % alpha sample size was calculated to be 374 by using Epi info software version 7.1.2.0. Stratified Simple random sampling technique used. Study tool: Sociodemographic profile recorded & depression was assessed with geriatric depression scale15. GCP and ethical guidelines followed as advised for human studies. Results and conclusion: The prevalence of depression risk in the study population was 20% (Females =26%, males=15%). Depression risk was seen statistically significantly associated with increasing age, female gender, absence of spouse support, economic dependence and type of family.